Increase of resting muscle stiffness, a less considered component of age-related skeletal muscle impairment - Lorenzo Marcucci; Carlo Reggiani (PAGEPress Publications, 2020)
Elderly people perform more slowly movements of everyday life as rising from a chair, walking, and climbing stairs. This is in the first place due to the loss of muscle contractile force which is even more pronounced than  the loss of muscle mass. In addition, a secondary, but not negligible, component is the rigidity or increased stiffness which requires greater effort to produce the same movement and limits the range of motion of the joints. In this short review, we discuss the possible determinants of the limitations of joint mobility in healthy elderly, starting with the age-dependent alterations of the articular structure and focusing on the increased stiffness of the skeletal muscles. Thereafter, the possible mechanisms of the increased stiffness of the muscle-tendon complex are considered, among them changes in the muscle fibers, alterations of the connective components (extracellular matrix or ECM, aponeurosis, fascia and tendon) and remodeling of the neural pattern of muscle activation with increased of antagonist co-activation.